The differential expression of alternatively spliced transcripts and imprinting status of MEG9 gene in cows. (24th July 2014) - Zhang, Kun; Li, Dongjie; Wang, Mengnan; Wu, Guojiang; Shi, Yunjiao; Li, Shijie
Summary Meg9/Mirg (maternally expressed gene 9/microRNA containing gene), a non‐coding RNA (ncRNA) comprising many alternatively splicing isoforms, has been identified as maternally expressed in mouse and sheep, but its imprinting status and splicing variants are still unknown in cattle. In this study, we found three splicing variants of the cattle MEG9 gene expressed in a tissue‐specific manner. A single nucleotide polymorphism site (SNP c.1354C>G) was identified in exon 3 of cattle MEG9 and used to distinguish between monoallelic and biallelic expression. Our results showed that MEG9 exhibited monoallelic expression in all examined cattle tissues by comparing sequencing results between genomic DNA and cDNA levels at the c.1354C>G SNP site, suggesting that MEG9 is imprinted in cattle.